Mountains of water the terraces and traditions of the Ifugao (Bookmark Video and Moving Images, 1999)
A documentary film which tells about the rich northern mountains of Cordillera enriched by the Ifugao's genius creation of the eight wonder of the world, the Banaue Rice Terraces, built a hundred years ago. Discover how the early Ifugaos go about their daily lives as this documentary highlights their unique and fascinating beliefs, rituals, arts and traditions.